Total ensiled diet containing forage palm replacing sorghum meal - Teixeira, Fábio Andrade (2022)
The objective of this study was to evaluate the substitution of sorghum meal per palm associated with Brachiaria decumbens as a bulk source in total feed silages. The experimental design was a completely randomized design, with four treatments (0, 33,3, 66,6 and 100% inclusion of palm in the diet) and eight replications. Thirty-two experimental PVC silos, 10 cm in diameter and 50 cm in length, equipped with a Bunsen valve were used. Chemical-bromatological analyzes were carried out (DM, CP, ashes, EE, NDFap, ADF, lignin, TC and TDN), determination of pH, ammonia nitrogen, effluent loss, gas loss, dry matter losses and dry matter recovery of silages. Forage palm is an additive that improves silage characteristics. The replacement of 100% of sorghum bran by palm in total diet silage presents better values for pH and ammoniacal nitrogen, lower losses by gases, effluents and dry matter and increased recovery of dry matter, in addition to improving the chemical composition of the silages.